Cuidado humanizado no pré-natal: um olhar para além das divergências e convergências Humane prenatal care: beyond convergences and divergences - Maria de Fátima Mota Zampieri; Alacoque Lorenzini Erdmann (Instituto Materno Infantil de Pernambuco, 2010)
OBJETIVOS: compreender os significados do cuidado humanizado no pré-natal, as divergências, convergências e barreiras para sua efetivação na ótica de gestantes e profissionais. MÉTODOS: pesquisa qualitativa, exploratória, com 19 gestantes e 23 profissionais do ambulatório do Hospital Universitário e de uma unidade básica de saúde, guiada por pressupostos de Edgar Morin e interpretada pela hermenêutica dialética. Os dados foram coletados mediante entrevistas e observação participante. RESULTADOS: destacam-se como significados as categorias: cuidado pré-natal; cuidado centrado no ser humano, no seu protagonismo e na promoção da saúde; atenção integral à saúde da mulher; acessibilidade aos serviços de saúde; relações dialógicas entre gestantes e profissionais; ambiente e profissionais humanizados e postura ética do profissional. As principais barreiras encontradas foram: questões socioeconômicas e pessoais das gestantes; formação biomédica; desarticulação entre os serviços de saúde; desvalorização da atenção primária e do profissional; poder; desatenção e desrespeito à gestante. CONCLUSÕES: o estudo aponta para um modelo de saúde humanístico centrado no ser humano e no seu protagonismo; evidencia o cuidado integral e ético; mostra entraves do sistema de saúde e da sociedade para concretizar o ideário da humanização, superáveis pelo empenho político e profissional, pela formação de redes solidárias entre serviços de saúde e mobilização social; amplia a produção de conhecimento e subsidia mudanças na prática. OBJECTIVES: to investigate how the understanding of pregnant women and health professionals with regard to humane prenatal care diverges or converges and to identify obstacles to its introduction. METHODS: a qualitative, exploratory method was employed with a sample of 19 pregnant women and 23 health professionals at the outpatient clinic of a teaching hospital and at a basic health care unit. The study was guided by the precepts of Edgar Morin and interpreted using dialectical hermeneutics. The data were collected in the course of interviews and participant observations. RESULTS: the main categories mentioned were: prenatal care; care based on the human individual, his or her involvement in the process, and health promotion; all-round women's health care; access to health services; communication between pregnant women and health professionals; the environment and the humane and ethical posture of the health professional. The main obstacles encountered were: the socio-economic status and personal problems of the pregnant women; biomedical training; break-down of communication between different health services; lack of respect for primary health care and the professionals delivering this service; power relations; failure to pay due attention and respect to the pregnant woman. CONCLUSIONS: the study points to the need for humane health care that involves the patient; involving all-round health care and ethical considerations. It also demonstrates the obstacles that exist, both in the health-care system and in society at large. These can only be overcome by increased commitment on the part of policy-makers and health professionals, the creation of social networks that involve both health services and the general public, and further research to generate knowledge and encourage changes in medical practice.